EVALUASI PERENCANAAN SALURAN PRIMER IRIGASI LAHAN PERTANIAN DUSUN GARUTU DESA BUTTU BATU KECAMATAN ENREKANG KABUPATEN ENREKANG - Marheni; Arsyad; Saleh (STKIP Subang, 2026)
The availability of irrigation water is an essential factor in increasing agricultural productivity and supporting sustainable farming activities. Garutu Hamlet, Buttu Batu Village, Enrekang District, Enrekang Regency has an agricultural area of 22.08 hectares; however, the distribution of irrigation water has not been optimal. Therefore, the planning of a primary irrigation canal is required to ensure an effective and equitable water supply.The data consisted of primary data obtained from field surveys and existing canal measurements, as well as secondary data including rainfall records from 2015–2024, climatological data, topographic maps, and agricultural land area. The analyses included the determination of design rainfall (R80), dependable discharge (Q80), Net Field Requirement (NFR), and the design of the primary irrigation canal using the Manning equation.The results indicate that the design rainfall (R80) is 312.48 mm, the average dependable discharge (Q80) is 0.469 m³/s, and the maximum irrigation water requirement is 0.138 m³/s with an irrigation efficiency of 61.2%. Based on the hydraulic analysis, the proposed trapezoidal primary irrigation canal has a bottom width of 0.80 m, a flow depth of 0.55 m, a freeboard height of 0.60 m, a total canal depth of 1.15 m, a side slope of 1:1, and a longitudinal bed slope of 0.021. The designed canal has a discharge capacity of 0.543 m³/s with a flow velocity of 0.73 m/s, indicating that it is capable of safely conveying the required irrigation discharge throughout the year. Therefore, the proposed canal dimensions satisfy the technical design requirements and are expected to improve water distribution efficiency and support increased agricultural productivity in Garutu Hamlet.